Rab31-dependent regulation of transforming growth factor ß expression in breast cancer cells - Soelch, Susanne; Beaufort, Nathalie; Loessner, Daniela; Kotzsch, Matthias; Reuning, Ute; Luther, Thomas; Kirchner, Thomas; Magdolen, Viktor (Molecular medicine (Cambridge, Mass.), 2021)
Background The small GTP-binding protein Rab31 plays an important role in the modulation of tumor biological-relevant processes, including cell proliferation, adhesion, and invasion. As an underlying mechanism, Rab31 is presumed to act as a molecular switch between a more proliferative and an invasive phenotype. This prompted us to analyze whether Rab31 overexpression in breast cancer cells affects expression of genes involved in epithelial-to-mesenchymal transition (EMT)-like processes when compared to Rab31 low-expressing cells. Methods Commercially available profiler PCR arrays were applied to search for differentially expressed genes in Rab31 high- and low-expressing CAMA-1 breast cancer cells. Differential expression of selected candidate genes in response to Rab31 overexpression in CAMA-1 cells was validated by independent qPCR and protein assays. Results Gene expression profiling of key genes involved in EMT, or its reciprocal process MET, identified 9 genes being significantly up- or down-regulated in Rab31 overexpressing CAMA-1 cells, with the strongest effects seen for TGFB1 , encoding TGF-ß1 (> 25-fold down-regulation in Rab31 overexpressing cells). Subsequent validation analyses by qPCR revealed a strong down-regulation of TGFB1 mRNA levels in response to increased Rab31 expression not only in CAMA-1 cells, but also in another breast cancer cell line, MDA-MB-231. Using ELISA and Western blot analysis, a considerable reduction of both intracellular and secreted TGF-ß1 antigen levels was determined in Rab31 overexpressing cells compared to vector control cells. Furthermore, reduced TGF-ß activity was observed upon Rab31 overexpression in CAMA-1 cells using a sensitive TGF-ß bioassay. Finally, the relationship between Rab31 expression and the TGF-ß axis was analyzed by another profiler PCR array focusing on genes involved in TGF-ß signaling. We found 12 out of 84 mRNAs significantly reduced and 7 mRNAs significantly increased upon Rab31 overexpression. Conclusions Our results demonstrate that Rab31 is a potent modulator of the expression of TGF-ß and other components of the TGF-ß signaling pathway in breast cancer cells.